Oxidase-mimicking activity of ultrathin MnO2 nanosheets in a colorimetric assay of chlorothalonil in food samples. (30th November 2020) - Sheng, Enze; Lu, Yuxiao; Tan, Yuting; Xiao, Yue; Li, Zhenxi; Dai, Zhihui
Highlights: A simple, rapid colorimetric method using MnO2 nanosheets was developed to detect chlorothalonil. The sterilization mechanism of chlorothalonil by construction of sensor was used for the first time. The method presented a low detection limit and significantly shortened the measurement time. Abstract: Chlorothalonil is a class of 2B carcinogen which is widely used in the prevention and treatment of fungal diseases in food samples. Its residual problem has been increasingly concerned by society. In this paper, a fast and simple colorimetric assay based on Manganese dioxide nanosheets (MnO2 NSs)-oxidize 3, 3′, 5, 5′-tetramethylbenzidine (TMB) platform was used to detect residual pesticide chlorothalonil in food samples. Under optimal conditions, the half maximal inhibitory concentration and the limit of detection of chlorothalonil were 3.27 and 0.024 ng/mL. There were no obvious cross-reactivity between chlorothalonil and interference substances. The recoveries shown the satisfactory results. The results of colorimetric assay for the authentic samples were largely consistent with gas chromatography. Therefore, the proposed method would be convenient and satisfactory analytical methods for the monitoring of chlorothalonil. Furthermore, the MnO2 – TMB system was used to produce test strips for quick and convenient visual detection of chlorothalonil with good performance.